Prevention of venous thromboembolic events in patients with lower leg immobilization after trauma: Systematic review and network meta-analysis with meta-epsidemiological approach. - D Douillet; C Chapelle; E Ollier; P Mismetti; P-M Roy; S Laporte (PLoS Medicine, 2022)
Background Lower limb trauma requiring immobilization is a significant contributor to overall venous thromboembolism (VTE) burden. The clinical effectiveness of thromboprophylaxis for this indication and the optimal agent strategy are still a matter of debate. Our main objective was to assess the efficacy of pharmacological thromboprophylaxis to prevent VTE in patients with isolated temporary lower limb immobilization after trauma. We aimed to estimate and compare the clinical efficacy and the safety of the different thromboprophylactic treatments to determine the best strategy. Methods and findings We conducted a systematic review and a Bayesian network meta-analysis (NMA) including all available randomized trials comparing a pharmacological thromboprophylactic treatment to placebo or to no treatment in patients with leg immobilization after trauma. We searched Medline, Embase, and Web of Science until July 2021. Only RCT or observational studies with analysis of confounding factors including adult patients requiring temporary immobilization for an isolated lower limb injury treated conservatively or surgically and assessing pharmacological thromboprophylactic agents or placebo or no treatment were eligible for inclusion. The primary endpoint was the incidence of major VTE (proximal deep vein thrombosis, symptomatic VTE, and pulmonary embolism-related death). We extracted data according to Preferred Reporting Items for Systematic Reviews and Meta-analyses for NMA and appraised selected trials with the Cochrane review handbook. Fourteen studies were included (8,198 patients). Compared to the control group, rivaroxaban, fondaparinux, and low molecular weight heparins were associated with a significant risk reduction of major VTE with an odds ratio of 0.02 (95% credible interval (CrI) 0.00 to 0.19), 0.22 (95% CrI 0.06 to 0.65), and 0.32 (95% CrI 0.15 to 0.56), respectively. No increase of the major bleeding risk was observed with either treatment. Rivaroxaban has the highest likelihood of being ranked top in terms of efficacy and net clinical benefit. The main limitation is that the network had as many indirect comparisons as direct comparisons. Conclusions This NMA confirms the favorable benefit/risk ratio of thromboprophylaxis for patients with leg immobilization after trauma with the highest level of evidence for rivaroxaban. Trial registration PROSPERO CRD42021257669.